AUGMENTED REALITY BASED LEARNING MEDIA IN FOTOSYNTHESIS MATERIAL - Putri, Kharisma Eka; Wiguna, Frans Aditia (Perkumpulan Pendidik IPA Indonesia (PPII), 2020)
This article contains the results of the design of learning media development based on Augmented Reality (AR) by bringing up virtual objects that use pointer markers. The purpose of this study is to obtain a design of learning media application on material of Photosynthesis based on Augmented Reality. Test this media using a usability measurement tool to measure success and obtain input from users. The results obtained from the design of learning media applications on photosynthetic material based on Augmented Reality are making it easy for users to use real interactions with the percentage of usability obtained by 91.25% and positive responses in the form of user input to interaction techniques in the Augmented Reality media so that input can used to improve the nextÂ media development.Keywords: Augmented Reality 1, photosynthesis 2, usability 3